From the Book Market to the Military Camp: a study about the dissemination of the ‘Aeneid’ in the Roman Empire from the point of view of the ‘exercitationes scribendi’ - Mota, Thiago Eustáquio Araújo (Romanitas - Revista de Estudos Grecolatinos, 2017)
According to the late ancient biographical tradition, Virgil expressed, before his death, the desire to incinerate the books of the Aeneid, since the work of composition was incomplete. Until the invention of the codex, the medium of dissemination of the Aeneid was, most likely, the volumen consisting of papyrus leaves. Considering the limitations of this medium, it is likely that the poem’s books circulated separately. Judging by the papyrological corpus (31 papyri identified until the present stage of the research), epigraphy and sporadic mentions by Latin authors, the epic reached a rapid spread within the limits of the Empire as early as the first two centuries of its publication (1st century BC). As part of the typology of the source and historical approach of the epic we are concerned in this article about a specific moment previous to the codices antiquores (4th-5th Century). Our approach concerns the problem of volumen support, as well as the diffusion of the Virgilian poems, in view of their poetic fruition and their school use from a group of papyri categorized as Exercitationes scribendi.
Keywords: Aeneid; Roman epic; Papyri; Latin paleography; Roman education; Archeology of text